OC-076 Outcomes after curative treatment for oesophago-gastric cancer in the elderly. (22nd June 2015) - Chadwick, G; Groene, O; Hardwick, R; Crosby, T; Riley, S; Cromwell, D
Abstract : Introduction: 60% of Oesophago-Gastric (OG) cancers are diagnosed in patients aged 70 or over. 1 The 2014 National Oesophago-Gastric cancer audit (NOGCA) report found that elderly patients were equally likely to be managed with curative intent (after adjusting for known confounders), but it is not clear whether their short term outcomes are comparable. In this study we investigated whether age was associated with outcomes after curative surgery. Method: This study uses data collected for the NOGCA, focusing on patients diagnosed between 1 st April 2011 and 31 st March 2013 who had a curative resection before the 1 st January 2014. Outcomes considered were 90 day mortality and complication rates. Results were adjusted for known confounders: sex, TNM stage at diagnosis, performance status, comorbidities and ASA grade. Results: Overall 13, 334 patients aged 70 or over were diagnosed with OG cancer. 28.8% of these were managed with curative intent, such that 1, 001 oesophagectomies and 1, 039 gastrectomies were performed in patients aged 70 or over. Patients aged 70 or over undergoing a curative oesophagectomy had higher 90-day mortality and complication rates than younger patients, this difference was maintained after adjusting for known confounders (Table 1 ). For gastrectomies there was no significance in outcomes according to the age of patient. Conclusion: Elderly patients undergoing an oesophagectomy had significantly worse outcomes compared to younger patients. Therefore efforts need to be made to reduce their higher risk to levels achieved by younger patients in future. Disclosure of interest: None Declared. Reference: Chadwick G, Taylor A, Groene O, et al . The National Oesophago-Gastric Cancer Audit. An audit of the care received by people with Oesophago-gastric cancer in England and Wales. 2014 Annual Report. In: HSCIC, ed., 20142014